Description of Sleep Quality of Students of the Nursing Department, Faculty of Sports and Health, Universitas Negeri Gorontalo at the Academic and Professional Stages - Nurdiana Djamaluddin (Jambura Nursing Journal, 2023)
In the process of becoming a nurse, nursing students need to go through two stages of education, namely the undergraduate stage of nursing (academic) and the professional stage (profession). These two stages of education have different learning loads and responsibilities. At the academic stage students will be equipped with nursing knowledge to then apply it at the professional stage to actual patients. This often results in poor sleep quality in nursing students. This study aims to describe the sleep quality of students majoring in nursing at Gorontalo State University. This study used a descriptive survey method with a sample of 545 respondents who were obtained using a total sampling technique. The research instrument used the Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quality. The results showed that there were 438 respondents (80.4%) who had poor sleep quality, and 107 respondents (19.6%) had good sleep quality. The conclusion of this study is that the majority of students majoring in Nursing at Gorontalo State University who are currently undergoing the lecture process have poor sleep quality.